1997
DOI: 10.2134/jeq1997.00472425002600060029x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Biosolids to Degraded Semiarid Rangeland: Nine‐Year Responses

Abstract: Rangeland restoration through surface application of biosolids (municipal sewage sludge) is an increasing practice. Biosolids supply both organic matter and available nutrients that are lacking in degraded rangeland soils. This study investigated the effects of biosolids applications of 0, 22.5, 45, and 90 Mg ha−1 to a degraded rangeland in 1985 on the soil chemical properties and N mineralization potentials 8 and 9 yr after the application, respectively. Following an initial increase in proportion to the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 0 publications
3
50
1
2
Order By: Relevance
“…After 11 yr, average yield on the 10, 15 and 20 cm topsoil removal treatments amended with manure was 87% of the undisturbed nonamended topsoil. White et al (1997) found that N mineralization potentials were significantly higher 9 yr after biosolid application to degraded rangeland in New Mexico. This indicated that soil fertility remained higher, even though most soil chemical indices were returning to those of untreated plots.…”
Section: Discussionmentioning
confidence: 93%
“…After 11 yr, average yield on the 10, 15 and 20 cm topsoil removal treatments amended with manure was 87% of the undisturbed nonamended topsoil. White et al (1997) found that N mineralization potentials were significantly higher 9 yr after biosolid application to degraded rangeland in New Mexico. This indicated that soil fertility remained higher, even though most soil chemical indices were returning to those of untreated plots.…”
Section: Discussionmentioning
confidence: 93%
“…Benth.) in New Mexico [14]. Other authors also found residual effects on soil nitrogen and available phosphorus after five years with biosolids applications from 40 to 120 Mg ha −1 rates compared to control rate in native grassland in Spain [29].…”
Section: Resultsmentioning
confidence: 88%
“…Biosolids rates from 18 to 45 Mg ha −1 have been recommended for arid rangelands with good agronomic results in terms of grass forage production and soil fertility [13]. Also, residual effects have been observed on soil fertility [14][15][16] and on forage production of arid grasslands [10,11]. However, limited information is available on the residual effects of biosolids application in semiarid grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…The negative impacts of the cutting and filling operations on soil productivity will need to be remediated by restoring natural ecological functions to the affected soils. Organic matter additions to the soil, such as biosolids and composts, decrease the bulk density of soils, increase infiltration rates and porosity, and contribute to better soil structure (Ruehlmann and Körschens 2009;Sloan and Cawthon 2003;White et al 1997). The use of cover crops can also be an important management tool for protecting soils from erosion during dormant seasons and for reestablishing key soil quality indicators (Abdollahi and Munkholm 2014;Stavi et al 2012).…”
Section: Conservation Recommendationsmentioning
confidence: 99%